Abordagem didática e uso dos conectores contrastivos em artigos de opinião de alunos do 9º ano: proposta de intervenção - Lima, Patrícia da Silva (2021)
The need for a contextualized teaching of grammar is already a consensus in the literature and in official documents. Nevertheless, the practice of grammar instruction in schools has not yet reached the ideal recommended by the National Curricular Parameters and by the recent Common National Curricular Base. The teaching of connectives, for instance, despite their role in text production, is usually limited to the identification of conjunctions and the classification of clauses in accordance with the grammatical tradition (LIMA, 2011; BECHARA, 2009). In the field of Linguistics, especially in Functionalism and Textual Linguistics, the argumentative and cohesive value of connectors is widely recognized (KOCH, 2011; NEVES, 2011b). Contrastive connectors, in particular, have the function to structure the argumentation, introducing arguments and counter-arguments. According Neves (2011a), connectors of opposition and concession can express various semantic relations, such as opposition, restriction, inference negation, contrast, compensation. Such relations can be seen in a continuum of opposition and admission, which goes from a minimum degree of opposition, when there is only an inequality between the terms, to a maximum degree of opposition, when the second clause cancels the first. It also starts from a minimum degree of admission, which is the recognition of the existence of the argument of the first sentence to a maximum degree that constitutes the concession. In order to diagnose the teaching/learning of connectives in the final years of Elementary School, we conducted an exploratory research that evaluated the use of connectives in 27 opinion articles produced by 9th grade students from a public school in Fortaleza and 381 activities about connectives taken from 8th and 9th grade Portuguese language textbooks from two collections of PNLD-2020. In the analysis of the activities, the type of question (metalinguistic, epilinguistic, productive, and normative); the axes of grammar teaching (VIEIRA, 2017); and the type of connective were taken into consideration. The results showed that (1) students rarely use connectives to explain meaning relations; (2) the only connector of opposition used in the students' productions was but, which demonstrates the students' low repertoire of connectors and, at the same time, reaffirms the prototypical character of the conjunction but; (3) contrastive connectors are explored in 11.5% of the total activities on connectives, which reinforces their degree of importance; (4) most of the questions focus on the use of contrastive connectors in a given context; (5) linguistic heterogeneity is hardly explored in the activities concerning connectors in general and contrastive connectors in particular. These data justify a pedagogical intervention that aims to expand the repertoire of contrastive connectors and the appropriateness of their use, especially in opinion articles. To this end, we present a pedagogical proposal consisting of seven workshops that deal with the recognition and appropriate use of opposition and contrast connectors in opinion articles. It is a pedagogical manual that can be adapted to each teacher's reality, and that allows the exploration of contrastive connectors in the three axes of grammar teaching: (1) systematicity; (2) interactivity and (3) heterogeneity. Thus, this work represents a contribution to the teaching of the grammar teaching based on the development of communicative competence.